Vibration Control for Spatial Aerial Refueling Hoses With Bounded Actuators - Liu, Zhijie; He, Xiuyu; Zhao, Zhijia; Ahn, Choon Ki; Li, Han-Xiong (IEEE transactions on industrial electronics (1982), 2021)
This article presents a control scheme for stabilizing a vibrating flexible hose used for aerial refueling subject to bounded actuators for the rate and magnitude. A dynamical model of hose systems is captured by partial differential equations (PDEs). Based on the PDE model, a novel boundary control law is proposed to dampen the flexible hose's vibration. The backstepping approach is utilized to devise the control scheme, with the bounded input magnitude and derivative handled by adopting the smooth hyperbolic tangent function. The Lyapunov criterion is exploited to demonstrate the stability of the controlled system. Finally, simulation results are used to evaluate the validity of the derived scheme.